UPAYA PENINGKATAN KEMAMPUAN BERPIKIR ANALISIS MATEMATIKA MELALUI MODEL MAKE A MATCH SISWA SEKOLAH DASAR - Febiana, Cindy; Purbasari, Imaniar; Riswari, Lovika Ardana (LPPM Universitas Bina Bangsa, 2024)
The aim of the research is to determine the application of the Make A Match model as an effort to improve the mathematical analytical thinking skills of class IV students at SDN 5 Tegalrejo in corner material with the help of paired cards. This research method is classroom action research on 21 class IV students at SDN 5 Tegalrejo. Collection techniques through pre-cycles, model application, evaluation tests, observation of learning activities and interviews. The results of the research showed an increase in the mathematical analysis thinking skills of fourth grade students at SDN 5 Tegalrejo in applying the Make A Match model with the help of paired cards in corner material. The scores obtained in the Pre-cycle were with a class average of 62.85, the first cycle had a class average of 72.61, and the second cycle had a class average of 88.09. Increasing mathematical analysis skills takes place in mathematical problem-solving activities through paired cards and evaluation of cycle I and cycle II through the ability to differentiate, organize and attribute. Students are able to achieve analytical thinking skills when the student's score has successfully achieved 3 indicators of students' analytical thinking skills, namely differentiating, organizing and attributing. Students gain knowledge of the concept of angles through understanding problems and surrounding angles, organizing mathematical and applied problems and making attributions in mathematical problems. The percentage of students' analytical thinking ability is achieved if it exceeds ≥ 60% of the classical percentage of students in the high category